Higher Elevations Tend to Have Higher Proportion of Plant Species With Glandular Trichomes - Wu, Rui; Lev-Yadun, Simcha; Sun, Lu; Sun, Hang; Song, Bo (Frontiers in Plant Science, 2021)
Glandular trichomes are well known to participate in plant chemical and physical defenses against herbivores, especially herbivorous insects. However, little is known about large-scale geographical patterns in glandular trichome occurrence. Herbivory pressure is thought to be higher at low elevations because of warmer and more stable climates. We therefore predicted a higher proportion of species with glandular trichomes at low elevations than at higher elevations. We compiled glandular trichome data (presence/absence) for 6,262 angiosperm species from the Hengduan Mountains (a global biodiversity hotspot in southwest China). We tested the elevational gradient (800-5,000 m a.s.l.) in the occurrence of plant species with glandular trichomes, and its correlations with biotic (occurrence of herbivorous insects) and abiotic factors, potentially shaping the elevational gradient in the occurrence of glandular trichomes. We found a significantly positive relationship between elevation and the occurrence of glandular trichomes, with the proportion of species having glandular trichomes increasing from 11.89% at 800 m a.s.l. to 17.92% at above 4,700 m. This cross-species relationship remained significant after accounting for phylogenetic relationships between species. Herbivorous insect richness peaked at mid-elevations and its association with the incidence of glandular trichomes was weak. Mean annual temperature was the most important factor associated negatively with glandular trichomes. Our results do not support the hypothesis that plant defenses decrease with increasing elevation. In contrast, a higher proportion of plant species with glandular trichome toward higher elevations is observed. Our results also highlight the importance of considering the simultaneous influences of biotic and abiotic factors in testing geographical variation in multifunctional plant defenses.